2008
DOI: 10.1002/bjs.6229
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure during endovascular aneurysm repair

Abstract: Radiation doses administered during EVAR were higher than previously thought, with a potential risk of radiation-induced skin damage and later malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
87
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 15 publications
8
87
0
1
Order By: Relevance
“…The DAP values for our patients were on average much larger than those reported by Geijer et al [16], but very similar to those reported by Weiss et al [17] and by Weerakkody et al [18]. The dosimetric parameters from our study and from three studies reported in the literature are compared in Table 1.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The DAP values for our patients were on average much larger than those reported by Geijer et al [16], but very similar to those reported by Weiss et al [17] and by Weerakkody et al [18]. The dosimetric parameters from our study and from three studies reported in the literature are compared in Table 1.…”
Section: Discussionsupporting
confidence: 88%
“…The median value (17 min) for time of procedure is, however, comparable to that in other studies [16][17][18]. As in some other studies [17,[22][23][24], we found a weak correlation (r 2 50.37) between DAP and fluoroscopy time.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Kuhelj, et al (2010) analyzing the dosimetric data on 179 patients treated using a suboptimal mobile C-arm unit found a 0.44 Gy median PSD (range 0.12 to 2.7 Gy). Investigators at Cabridge reported a 0.85 Gy median PSD on 96 repairs (Weerakkody, et al 2008;. About 1/4 of their patients received PSD higher than 3.75 Gy and the maximum dose was 8.8 Gy (the authors excluded from the analysis data on seven additional repairs because the "values were orders of magnitude greater than typical values recorded").…”
Section: Assessment Of Deterministic Effects To Patientmentioning
confidence: 99%